Emissive spin-0 triplet-pairs are a direct product of triplet-triplet annihilation in pentacene single crystals and anthradithiophene films - Bossanyi, David G.; Matthiesen, Maik; Wang, Shuangqing; Smith, Joel; Kilbride, Rachel C.; Shipp, James D.; Chekulaev, Dimitri; Holland, Emma; Anthony, John E.; Zaumseil, Jana; Musser, Andrew J.; Clark, Jenny (Nature chemistry, 2021)
Singlet fission and triplet-triplet annihilation represent two highly promising ways of increasing the efficiency of photovoltaic devices. Both processes are believed to be mediated by a biexcitonic triplet-pair state, 1(TT). Recently however, there has been debate over the role of 1(TT) in triplet-triplet annihilation. Here we use intensity-dependent, low-temperature photoluminescence measurements, combined with kinetic modelling, to show that distinct 1(TT) emission arises directly from triplet-triplet annihilation in high-quality pentacene single crystals and anthradithiophene (diF-TES-ADT) thin films. This work demonstrates that a real, emissive triplet-pair state acts as an intermediate in both singlet fission and triplet-triplet annihilation and that this is true for both endo- and exothermic singlet fission materials.